Development and fluctuation of crystal orientation fabric in the deep sections of the Dome Fuji ice core, Antarctica: impacts of dust particles and migration recrystallization - T. Saruya; A. Miyamoto; S. Fujita; S. Fujita; K. Goto-Azuma; K. Goto-Azuma; M. Hirabayashi; A. Hori; M. Igarashi; Y. Iizuka; T. Kameda; H. Ohno; et al. (The Cryosphere)
This study investigated the crystalline textural properties of an Antarctic deep ice core with a length of 3035 m acquired from an inland plateau dome, with a focus on depths below 2400 m. The cluster strength of the c axes was ascertained using the dielectric tensor method to assess the bulk properties of thick sections, and detailed orientation distributions of the c and a axes were determined using the Laue X-ray diffraction technique. The c- and a-axis fabric data were compared with various other characteristics of the same ice core. Microstructural observations were made using optical microscopy. The clustering strength of the single-pole c-axis fabric was at a maximum at depths between 2400 and 2640 m. The relationship between the cluster strength and the concentration of dusty impurities was found to change at approximately 2640 m, and fluctuations in strength increased significantly below this depth. Impurity-rich layers maintained a high degree of clustering, whereas layers with fewer impurities showed relaxation. The latter layers also exhibited evidence of nucleation and grain boundary migration. In ice such as this, the degree of a-axis organization was increased with one or two sets of three preferred orientations. Dynamic recrystallization evidently played a critical role, with more pronounced effects in impurity-poor layers than in impurity-rich layers. This phenomenon promoted the relaxation of the c-axis clustering, deformation based on dislocation creep and organization of the a axis. Below 2580 m, the angles of inclination of the c-axis cluster and layers deviated significantly from the vertical, suggesting that the system rotated as a rigid body as a result of simple shear.